Effect of n-butanol and diethyl ether as oxygenated additives on combustion–emission-performance characteristics of a multiple cylinder diesel engine fuelled with diesel–jatropha biodiesel blend. (April 2015) - Imtenan, S.; Masjuki, H.H.; Varman, M.; Rizwanul Fattah, I.M.; Sajjad, H.; Arbab, M.I.
Highlights: Viability of oxygenated additives to improve jatropha biodiesel–diesel blend. Performance, emission and combustion analysis at different conditions. Physicochemical properties of the blends improved with the additives. 10% additive blends performed better than 5% additive blends. Diethyl ether performed better than n -butanol regarding engine performance. Abstract: Jatropha biodiesel is considered as one of the most prospective renewable energy sources of Malaysia in recent years. Hence, an investigation was conducted for the improvement of jatropha biodiesel–diesel blend with the addition of 5–10% n -butanol and diethyl ether by vol. which are commonly known as oxygenated cold starting additive. Engine tests were conducted at variable speed, ranging from 1000 rpm to 3000 rpm at constant 80 N m torque on a 4-cylinder turbocharged indirect injection diesel engine. Engine performance parameters like brake specific fuel consumption, brake specific energy consumption, brake thermal efficiency and engine emissions like carbon monoxide, unburned hydrocarbons, nitrogen oxide and smoke opacity were measured. Performance and exhaust emissions variation of the modified blends from the baseline fuel (jatropha biodiesel–diesel blend) were compared for the assessment of the improvement quantitatively. In-cylinder pressure diagram of all the test fuels were acquired and the heat release rate analysis was conducted at different operating conditions to explore the features of combustion mechanism and correlate them with the performance and emission characteristics to acquire better understanding of the scenario. However, in a nut-shell, the investigation reveals the potential of n -butanol and diethyl ether to be used as the additive of jatropha biodiesel–diesel blend in the context of combustion, performance and emission characteristics.